Business challenges among halal cosmetic and personal care entrepreneurs - Hafeez, Muhammad Haroon; Arshad, Rozita (2016)
The growth of halal cosmetic and personal care industry encourage the entrepreneur cosmetic and personal care applying halal certification standard to increase their business performance. Yet, a study and efforts to explain halal cosmetic and personal care challenges remain scant compared to other halal product such as food, slaughter, and financial banking system.This conceptual paper explores the business challenges faced by the entrepreneurs in halal cosmetic and personal care. The source of this study based on a library study review from available statistics, annual reports as well as reliable articles. Overall, there are several challenges faced by entrepreneurs in this industry that is fulfill consumer demand, understanding shariah requirement, market competition, and organization capability.